Islamic Education Values in Shaping Washatiy Attitudes At Thursina High School Malang - safi'i, imam; Maskuri; Djunaidi Ghoni (The Islamic Education and Multiculturalism Foundation, 2023)
Abstract The diversity that exists in the Thursina Malang institution can be seen from the background of the origin of the Thursina Malang students, some are from various ethnic groups and cultures in Indonesia, they are from Kalimantan, Sulawesi, East Java, Central Java, Madura and Sumantra. Thursina's students are not only diverse in origin, but also the backgrounds of their parents are very varied, ranging from families of academics, businessmen, elite government officials and ordinary people. Thursina's students are not only diverse in terms of regional origin, but also the backgrounds of their parents who vary greatly from academics, businessmen, elite government officials and ordinary people. Even though the students come from various backgrounds, they can live side by side well because differences are considered very common, and at the Thursina institution, the mission of outvalues ​​is broad knowledge, has moderate thoughts in Islam and has an understanding and attitude of rahmatanlilalamin. This study aims to describe, analyze and provide an interpretation of the values ​​of Islamic education that are used as the basis for forming wasathiy attitudes at Thursina High School Malang. This research uses a qualitative approach with the type of case study. Data collection techniques through observational studies, interviews and documentation. Data analysis used the Miles and Huberman interactive model analysis. checking the validity of the data through construct validity, internal validity, external validity and consistency. The results showed that in forming students to have a washatiy attitude at Thursina Malang high school, several Islamic educational values are applied, such as; the value of commitment, the value of being virtuous (maintaining integrity and morality), the value of empathy (sensitive to surrounding problems), the value of compassionate (love others wholeheartedly), the value of excellent in service (leading in helping others), the value of moderate (wise and respecting differences), the value of Rahmatan lilalamin (spreading kindness and benefits to others) Keywords: Values, Islamic education, Thursina High School